COMPARATIVE LEGAL ANALYSIS OF FOREIGN COUNTRIES WITH UZBEKISTAN IN THE SPHERE OF CYBER SECURITY AND SOME CONCLUSIONS (Conferencea, 2022)
This thesis deals with issues in the field of the information society and information security. In addition, a comparative analysis of the legal practice of foreign countries is carried out and methods for resolving the problems that have arisen in ensuring cybersecurity are considered. And also based on the study, some conclusions were drawn and recommendations were given